ANALYSIS OF GEOGRAPHICAL TERMS (American Journal of Interdisciplinary Research and Development, 2022)
The article deals with the interpretation of widespread geographical terms in the Ferghana Valley. In the case of these local terms, it is clear that they are diverse and participate in the formation of toponyms.